A new approach to anticoagulant therapy: abelacimab and the EKOS ultrasonic endovascular thrombectomy system - V. N. Ardashev; V. M. Frolov; E. M. Novikov; M. M. Stepanov; E. I. Myasoedova; V. V. Dordjieva; E. A. Gerasimenko; I. V. Globa (Clinical Medicine (Russian Journal), 2026)
The article focuses on new approaches to anticoagulation: abelacimab, a modern, highly selective factor XI inhibitor, and the Boston Scientifi c EKOS minimally invasive clot dissolution system. This paper analyzes the unique mechanisms of action of abelacimab, revealing its therapeutic potential compared to traditional anticoagulants, and its potential applications in clinical practice. The drug's pharmacokinetic properties are discussed in detail, particularly its rapid onset of action (within 30 minutes) and exceptional duration of action (over 30 days). Particular attention is paid to the clinical indications for abelacimab, as well as its pharmacokinetic characteristics and administration routes, which are important aspects for its practical application. The second part of the article discusses the potential use of the Boston Scientifi c EKOS ultrasound endovascular thrombectomy system for minimally invasive thrombolysis, which can be combined with the eff ectiveness of abelacimab. A clinical example of the successful use of the EKOS system in a patient with occlusive deep vein thrombosis of the lower extremity is presented.